2010
DOI: 10.1002/cssc.200900180
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Heterogeneous Catalysis for Sustainable Chemistry

Abstract: The current established catalytic processes used in chemical industries use metals, in many cases precious metals, or metal oxides as catalysts. These are often energy-consuming and not highly selective, wasting resources and producing greenhouse gases. Metal-free heterogeneous catalysis using carbon or carbon nitride is an interesting alternative to some current industrialized chemical processes. Carbon and carbon nitride combine environmental acceptability with inexhaustible resources and allow a favorable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
382
1
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 565 publications
(398 citation statements)
references
References 133 publications
3
382
1
12
Order By: Relevance
“…4, the representative AFM image shows a uniform thickness of about 0.38 nm. This thickness agrees well with the theoretical values of single-layer carbon nitride (0.324 nm) [14,15]. This can be used as a strong evidence for the presence of g-C3N4 nanosheets in the presence of monatomic layers in mixed solvents.…”
Section: Characterization Of Physiochemical Properties Of G-c 3 N 4 Nsupporting
confidence: 89%
“…4, the representative AFM image shows a uniform thickness of about 0.38 nm. This thickness agrees well with the theoretical values of single-layer carbon nitride (0.324 nm) [14,15]. This can be used as a strong evidence for the presence of g-C3N4 nanosheets in the presence of monatomic layers in mixed solvents.…”
Section: Characterization Of Physiochemical Properties Of G-c 3 N 4 Nsupporting
confidence: 89%
“…Recently, it was reported that metals as catalyst in ORR only promote the formation of active sites and have no role in catalytic function [77]. Chemically modified carbon-based materials including carbon nanotubes, graphene, graphite foam can be used as catalyst for ORR [78,79]. ORR can proceed to four electron pathway using a nitrogen incorporated catalysts [80][81][82].…”
Section: Cathode With Metal-free Catalystmentioning
confidence: 99%
“…The use of carbon catalysts is attractive in this regard because of their low cost and natural abundance [4][5][6][7][8] . Carbocatalysis is well established in the oxidative dehydrogenation of ethylbenzene to produce styrene 4 . Oxidative aromatization involving a molecular oxygen and activated carbon system has also been used to prepare aromatic compounds such as pyrazoles, pyridine, indoles and so on 8 .…”
mentioning
confidence: 99%